A Cd-MOF fluorescence sensor with dual functional sites for efficient detection of metal ions in multifarious water environments. Issue 47 (15th November 2021) - Li, Jing; Zhao, Yun-Xiu; Wu, Qian; Yang, Hua; Lu, Jing; Ma, Hui-Yan; Wang, Su-Na; Li, Yun-Wu
Abstract : A 2D MOF displays high performance luminescence quenching for detecting Fe 3+ and Cu 2+ in pure water, actual river water and simulated HEPES with superior low LODs. Multiple experiments and DFT calculations co-verify a weak interaction quenching mechanism. Abstract : High-performance fluorescence sensors combining convenience, low cost and high sensitivity are prospective for water pollution and human health. Luminescent metal–organic frameworks (LMOFs) as sensors can meet these criteria for high efficient detection of toxic metal ions. Herein, a new LMOF LCU-109 has been fabricated by Sharpless in situ tetrazole synthesis system assisted by polycarboxylic O-donor ligand. It showed a 2D binodal (3, 6)-connected kgd structure with multiple N and O dual-functional sites for detecting guest metal ions. As expected, LCU-109 can be highly sensitive and selectively detect trace amounts of Fe 3+ and Cu 2+ ions in an aqueous solution by the luminescence quenching mechanism. Notably, the detection limits (LODs) of Fe 3+ and Cu 2+ ions are 0.0043 and 0.0028 ppm, respectively, in water, which are significantly lower than the minimum standards stipulated for drinking water by the World Health Organization (WHO) (0.3/2.0 ppm) and U.S. Environmental Protection Agency (USEPA) (0.3/1.2 ppm). Moreover, LCU-109 also shows excellent luminescent sensing activities for Fe 3+ and Cu 2+ ions in simulated HEPES biological system and actual river water with low LODs of 0.034/0.019 ppm and 0.0756/0.107 ppm, respectively, which is also lower than the standard of WHO and USEPA. Moreover, convenient and real-time naked eye detection effects are provided by the exquisitely made LCU-109 fluorescent test papers. Importantly, combining density functional theory (DFT) calculations with a variety of experiments, the fluorescence quenching mechanism for energy competitive absorption and weak interaction is further revealed.